Multicrystalline SiC formed body
By controlling the crystal grain size and nitrogen concentration within specific ranges and optimizing CVD film formation conditions, a polycrystalline SiC molded body with low volume resistivity is achieved, addressing the challenges faced in semiconductor manufacturing equipment applications.
Patent Information
- Application Number
- JP2024576751
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2044-06-03
AI Technical Summary
Existing polycrystalline SiC molded bodies face challenges in achieving low volume resistivity while maintaining controlled crystal grain size, which is crucial for applications in semiconductor manufacturing equipment.
The development of a polycrystalline SiC molded body with an average crystal grain size of 5.5 μm to 25.0 μm and nitrogen concentration between 0.27 x 10^20 Pcs/cm^3 and 5.4 x 10^20 Pcs/cm^3, along with a specific product of carrier density and hole mobility, is achieved through a CVD method with optimized film formation conditions, including a film formation rate of 15 μm/hr to 60 μm/hr and residence time of 10 seconds to 100 seconds.
This approach results in a polycrystalline SiC molded body with a low volume resistivity of 0.0200 Ω·cm or less, suitable for use as a heater in semiconductor manufacturing equipment, while maintaining controlled crystal grain size and nitrogen concentration.
Smart Images

Figure 0007669598000003 
Figure 0007669598000004 
Figure 0007669598000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycrystalline SiC molded body and a method for producing the same. [Background technology]
[0002] Polycrystalline SiC (silicon carbide) compacts have excellent mechanical strength properties, electrical properties, heat resistance, chemical stability, etc., and are used in various industrial applications. For example, polycrystalline SiC compacts are used in high-temperature and high-purity atmospheres. Common applications include dummy wafers and components for semiconductor manufacturing equipment, such as components constituting semiconductor manufacturing equipment.
[0003] For example, polycrystalline SiC compacts used as semiconductor manufacturing equipment components are generally in the form of plates. The main surface of the polycrystalline SiC molded body is the growth direction of the CVD film, and if the polycrystalline SiC molded body is plate-shaped, both the front and back surfaces can be main surfaces, except for the sides. The thickness of the polycrystalline SiC molded body varies depending on the film formation time, and it can be formed to any thickness. Discs with diameters of 100 mm to 300 mm are known.
[0004] Polycrystalline SiC molded bodies as semiconductor manufacturing equipment components can also be suitably used as cylindrical polycrystalline SiC molded bodies by forming a film on a rod-shaped substrate. In this case, the main surface of the polycrystalline SiC molded body is the growth direction of the CVD film, and if the polycrystalline SiC molded body is cylindrical, both the front and rear surfaces of the cylinder can be the main surface. The thickness of the polycrystalline SiC molded body varies depending on the film formation time, and can be formed to any thickness. Cylinders with diameters of 5 mm to 700 mm are known.
[0005] Regarding SiC molded bodies having a specific resistivity, Patent Document 1 describes a silicon carbide body for use as a semiconductor manufacturing member obtained by a CVD method, which is characterized in that the content of nitrogen element is 0.1 to 100 ppm, the content of metal elements other than silicon is 10 ppm or less, the resistivity is 0.01 to 10 Ω·cm, and the variation in the resistivity is 10% or less. As a specific example, a silicon carbide body having a resistivity of 0.1 to 5 Ω·cm is disclosed.
[0006] Patent Document 2 describes an independent article comprising chemically vapor deposited low resistivity silicon carbide having an electrical resistivity of less than 0.9 Ω·cm, and discloses, as a specific example, a silicon carbide deposit having a resistivity of 0.25 to 0.9 Ω·cm. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 4595153 [Patent Document 2] JP 2001-316821 A Summary of the Invention [Problem to be solved by the invention]
[0008] Incidentally, as a SiC compact, a small crystal grain size is preferable because general wear occurs preferentially from the grain boundaries, which leads to a reduction in particles generated during wear. Also, a large crystal grain size reduces the volume resistivity, making it suitable for use as a heater, among other semiconductor manufacturing equipment components.
[0009] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a polycrystalline SiC molded body having a low volume resistivity and in which the crystal grain size is controlled within a specific range, and a method for producing the same. [Means for solving the problem]
[0010] As a result of investigations, the present inventors have found that the above problems can be solved by the following means. [1] The average crystal grain size is 5.5 μm or more and 25.0 μm or less, and the nitrogen concentration is 0.27 × 10 20 pieces / cm 3 More than 5.4×10 20 pieces / cm 3 The product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 Polycrystalline SiC compact with a density of less than 1 / cmVsec. [2] The polycrystalline SiC molded body according to [1], having a volume resistivity of 0.0200 Ω·cm or less. [3] A method for producing a polycrystalline SiC molded body according to [1], comprising the steps of: placing a substrate in a CVD reactor; heating the substrate; and introducing a mixed gas containing a raw material gas and a nitrogen-containing gas into the CVD reactor and depositing a polycrystalline SiC film on the heated substrate by a CVD method, wherein the deposition step is carried out under conditions of a deposition rate of 15 μm / hr or more and 60 μm / hr or less and a residence time of 10 seconds or more and 100 seconds or less. Effect of the Invention
[0011] According to the present invention, there are provided a polycrystalline SiC molded body having a low volume resistivity in which the crystal grain size is controlled within a specific range, and a method for producing the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram showing an example of a manufacturing system for a polycrystalline SiC compact. [Diagram 2] FIG. 1 is a schematic diagram showing a modified example of a CVD reactor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] 1: Polycrystalline SiC molded body The polycrystalline SiC compact according to the embodiment of the present invention has an average crystal grain size of 5.5 μm or more and 25.0 μm or less, and a nitrogen concentration of 0.27×1020 pieces / cm 3 More than 5.4×10 20 pieces / cm 3 The product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 By adopting such a configuration, it is possible to obtain a polycrystalline SiC molded body having a low volume resistivity in which the crystal grain size is controlled within a specific range.
[0014] In this specification, the term "average crystal grain size" refers to the "average crystal grain size" calculated by the "area fraction method" determined by EBSD (Electron Backscatter Diffraction).
[0015] According to this embodiment, the average crystal grain size is 5.5 μm or more and 25.0 μm or less, and the nitrogen concentration is 0.27×10 20 pieces / cm 3 More than 5.4×10 20 pieces / cm 3 The product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 It is possible to obtain a polycrystalline SiC molded body having a density of less than 1 / cmVsec.
[0016] The average crystal grain size is, for example, 5.5 μm or more and 25.0 μm or less, preferably 8.0 μm or more and 20.0 μm or less, and more preferably 10.0 μm or more and 15.0 μm or less.
[0017] In this specification, "nitrogen concentration" refers to the number of nitrogen atoms per unit volume / cm 3 The nitrogen concentration is determined using dynamic SIMS (Secondary Ion Mass Spectrometry).
[0018] Nitrogen concentration is 0.27×10 20 pieces / cm 3 More than 5.4×10 20 pieces / cm 3A sufficiently small volume resistivity can be obtained by keeping the nitrogen concentration in the following range. This nitrogen concentration corresponds to 200 ppm or more and 3800 ppm or less.
[0019] Such a nitrogen concentration is an extremely large value as an impurity concentration doped into a polycrystalline SiC molded body, and is usually an amount that exceeds the solid solubility limit. If nitrogen is added in an amount that exceeds the solid solubility limit, a compound different from SiC is generated, and the function required of a polycrystalline SiC molded body cannot be exhibited. However, according to this embodiment, by the manufacturing method described below, nitrogen can be dissolved in solid solution while containing nitrogen at such a concentration, and the characteristics required of a polycrystalline SiC molded body can be satisfied. The reason why such characteristics are realized is not clear, but for example, if the film formation rate is excessively slow, the film formation time becomes long, so that the time for the generation of compounds different from SiC is also long, and it is considered that it is not possible to form a solid solution. In addition, if the film formation rate is excessively fast, SiC is formed before nitrogen is decomposed into a reactive intermediate, so that the nitrogen solid solution reaction does not occur sufficiently.
[0020] The "product of carrier concentration x Hall mobility" is a value calculated from the "carrier density" and the "Hall mobility."
[0021] The product of carrier density and Hall mobility is related to the volume resistivity. According to this embodiment, the product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 By setting the density to be equal to or less than particles / cmVsec, a sufficiently small volume resistivity can be obtained. Moreover, the polycrystalline SiC compact is preferably 25×10 20 pcs / cmVsec or more 100×10 20 Counts / cmVsec or less, more preferably 35×10 20 pcs / cmVsec or more 100×10 20 The product of carrier density×Hall mobility can be equal to or less than 1 / cmVsec.
[0022] "Carrier density" refers to the concentration of impurities doped into the SiC compact. The carrier density can be determined using Hall effect measurement.
[0023] For example, the carrier density is 1.0×10 19 pieces / cm 3 Above 7.0×10 19 pieces / cm 3 The following is the result.
[0024] "Hall mobility" is a well-known parameter and can be determined using Hall effect measurements. For example, the Hall mobility is 2 / Vsec or more 150cm 2 / Vsec or less.
[0025] According to this embodiment, the polycrystalline SiC body can have a volume resistivity of, for example, 0.0200 Ω·cm or less, preferably 0.0100 Ω·cm or less. Moreover, the polycrystalline SiC body can have a volume resistivity of, more preferably, 0.0010 Ω·cm or less, and further preferably, 0.0001 Ω·cm or less.
[0026] In one preferred embodiment, the polycrystalline SiC compact is 3C-SiC.
[0027] In a preferred embodiment, the polycrystalline SiC molded body has a main surface. The polycrystalline SiC molded body is preferably plate-shaped, more preferably disk-shaped. When the polycrystalline SiC molded body is plate-shaped, the main surface of the polycrystalline SiC molded body means the front and back surfaces excluding the side surfaces. In this case, the thickness of the polycrystalline SiC molded body is, for example, 0.1 mm or more and 5.0 mm or less, preferably 0.2 mm or more and 3.0 mm or less. In addition, the diameter of the polycrystalline SiC molded body when it is disk-shaped is not particularly limited, but is, for example, 100 mm or more and 300 mm or less, preferably 130 mm or more and 200 mm or less.
[0028] The polycrystalline SiC molded body may be cylindrical. When the polycrystalline SiC molded body is cylindrical, the main surface of the polycrystalline SiC molded body means the surface and inner surface of the cylinder. In this case, the thickness of the polycrystalline SiC molded body is, for example, 0.1 mm or more and 5.0 mm or less, preferably 0.2 mm or more and 3.0 mm or less.
[0029] In a more preferred embodiment, the primary surface has a (111) peak intensity ratio of 0.25 to 0.50. The "(111) peak intensity ratio" is a parameter that represents the ratio of the diffraction peak intensity of SiC(111) to the sum of the diffraction peak intensities of the SiC(111) plane, the SiC(200) plane, the SiC(220) plane, and the SiC(311) plane in an X-ray diffraction pattern.
[0030] 2: Manufacturing method of polycrystalline SiC compact A polycrystalline SiC molded body having the above-mentioned characteristics can be obtained by adjusting the film formation conditions, etc. in the manufacturing method described below. The manufacturing method of the polycrystalline SiC molded body according to this embodiment will be described below.
[0031] FIG. 1 is a schematic diagram showing an example of a manufacturing system used in the manufacturing method of the polycrystalline SiC compact according to the present embodiment. This manufacturing system is provided with a CVD reactor 1 and a mixer 2. In the mixer 2, a carrier gas 6, a raw material gas 7 serving as a supply source of SiC, and a nitrogen-containing gas 8 are mixed to generate a mixed gas. The mixed gas is supplied from the mixer 2 to the CVD reactor 1 at a "flow rate Q". A substrate 3 (e.g., a graphite substrate) is placed in the CVD reactor 1. In the CVD reactor 1, the substrate 3 is heated during operation. The substrate 3 is preferably disk-shaped or rod-shaped. In addition, a nozzle 4 is provided in the CVD reactor 1, and the mixed gas is introduced into the CVD reactor through this nozzle 4. When the mixed gas is introduced into the CVD reactor, a polycrystalline SiC film is formed on the heated substrate 3 by the CVD method. At this time, nitrogen derived from the nitrogen-containing gas is doped into the polycrystalline SiC film. That is, a polycrystalline SiC film doped with nitrogen is obtained. The substrate 3 is removed from the obtained polycrystalline SiC film, and the film is ground as necessary, to obtain a polycrystalline SiC compact.
[0032] In the example shown in Fig. 1, a plurality of nozzles 4 are provided. The substrate 3 is arranged vertically. The plurality of nozzles 4 are provided on both sides of the furnace wall so as to sandwich the substrate 3. In Fig. 1, L is the distance between the tip of each nozzle (the nozzle for ejecting the raw material gas) and the substrate 3.
[0033] It should be noted that the CVD reactor 1 does not necessarily have to have the configuration as shown in FIG. 1. FIG. 2 is a diagram showing a modified example of the CVD reactor 1. In the example shown in FIG. 2, a plurality of nozzles 4 are provided at the top of the CVD reactor 1. The substrate 3 is arranged horizontally. The CVD reactor 1 may have the configuration as shown in FIG. 2.
[0034] Possible embodiments of the CVD reactor include a cold-wall type and a hot-wall type. In a cold-wall type CVD reactor, the furnace wall and the atmosphere inside the furnace are not directly heated, and only the substrate is directly heated. In a hot-wall type CVD reactor, the entire furnace including the furnace wall and the atmosphere inside the furnace is heated. In this embodiment, there is no difference in the characteristics of the SiC molded body obtained by either the cold-wall type or the hot-wall type.
[0035] In this embodiment, the polycrystalline SiC film is formed at a specific "arrival time τ." Specifically, the formation is performed under conditions such that the arrival time τ is 0.02 seconds or more and 0.10 seconds or less.
[0036] The arrival time τ represents the time from when the mixed gas is introduced into the CVD reactor until it reaches the substrate. Specifically, the arrival time τ is calculated according to the following formula:
[0037] Arrival time τ=L / u L: Distance between the source gas outlet (nozzle tip) and the substrate u: Flow velocity of mixed gas in the reactor
[0038] The flow velocity u of the mixed gas is calculated by dividing the flow rate Q by the cross-sectional area A of the nozzle.
[0039] The flow rate Q represents the flow rate of the mixed gas between the mixer and the reactor. The flow rate Q is not particularly limited, but is, for example, 10 L / min to 400 L / min, preferably 50 L / min to 350 L / min.
[0040] According to the findings of the present inventors, the arrival time τ affects the concentration of dissolved nitrogen, and thus affects the carrier concentration and the Hall mobility. Therefore, by optimizing the arrival time τ, it is possible to realize a polycrystalline SiC film having a predetermined average particle size and in which the product of the nitrogen concentration and the carrier density × Hall mobility is controlled. The arrival time τ is preferably 0.02 seconds or more and 0.10 seconds or less, more preferably 0.02 seconds or more and 0.08 seconds or less, and even more preferably 0.02 seconds or more and 0.06 seconds or less, in order to adjust the particle size to a preferred range.
[0041] The raw material gas that serves as a supply source of SiC may be a one-component system (a gas containing Si and C) or a two-component system (a gas containing Si and a gas containing C).
[0042] For example, examples of one-component source gases include methyltrichlorosilane, trichlorophenylsilane, dichloromethylsilane, dichlorodimethylsilane, and chlorotrimethylsilane, etc. Examples of two-component source gases include mixtures of silane-containing gases such as trichlorosilane and monosilane with hydrocarbon gases, etc.
[0043] The nitrogen-containing gas may be any gas capable of doping nitrogen into the polycrystalline SiC film, for example, nitrogen gas.
[0044] The carrier gas used during film formation is not particularly limited, but may be, for example, hydrogen gas.
[0045] The film formation conditions other than the arrival time τ are not particularly limited, but for example, the following conditions can be adopted.
[0046] Regarding the heating temperature during film formation, the reaction temperature is, for example, 1300° C. to 1400° C., preferably 1300° C. to 1350° C. Note that the furnace walls and heat insulating materials in the furnace are preferably kept at a temperature at which SiC and decomposition products of the raw material gas do not accumulate (for example, 1000° C. or less, preferably 700° C. or less).
[0047] The flow rate of the nitrogen-containing gas is, for example, 5 vol% to 100 vol%, preferably 30 vol% to 50 vol%, of the total flow rate of the nitrogen-containing gas flow rate, the raw material gas flow rate, and the carrier gas flow rate.
[0048] The deposition rate is, for example, 15 μm / hr to 60 μm / hr, preferably 15 μm / hr to 40 μm / hr. By controlling the deposition rate within the above range, the average particle size and nitrogen concentration can be controlled to predetermined values.
[0049] The residence time is, for example, 10 seconds or more and 100 seconds or less, preferably 20 seconds or more and 75 seconds or less. The residence time means the time during which the mixed gas is retained in the reactor. By controlling the residence time within the above range, the average particle size can be controlled to a predetermined value. EXAMPLES
[0050] The present invention will be described in more detail below with reference to examples. In the examples and comparative examples, the film formation time was set to 1 hour or more and 60 hours or less, and the reaction temperature was set to 1200° C. or more and 1500° C. or less.
[0051] Example 1 A CVD reactor was prepared as shown in Figure 1. As a substrate, a single graphite substrate with a diameter of 160 mm and a thickness of 5 mm was prepared and placed in the CVD reactor.
[0052] Next, a polycrystalline SiC film was formed on the substrate under the conditions described in Table 1. Specifically, MTS (methyltrichlorosilane) was used as the raw material gas. H2 gas was used as the carrier gas. N2 gas was used as the nitrogen-containing gas. The raw material gas, carrier gas, and nitrogen-containing gas were mixed in a mixer 2 to generate a mixed gas. The mixed gas was supplied into a CVD reactor 1. The supply amount of the mixed gas was set to the value described as "gas amount" in Table 1. The concentrations of MTS gas, H2 gas, and N2 gas in the mixed gas were as described in Table 1.
[0053] The residence time was 22 seconds. The residence time was calculated according to the following formula.
[0054] Residence time (seconds) = (furnace volume / gas volume) x ((20 + 273) / (reaction temperature + 273)) x 60
[0055] The arrival time τ was 0.03 seconds.
[0056] After the film was formed, the graphite substrate was removed from the CVD reactor and subjected to peripheral processing and division processing. The graphite base material was then removed to obtain a polycrystalline SiC compact having a diameter of 150 mm and a thickness of 0.6 mm. The front and back surfaces were then ground by a surface grinding process to obtain a polycrystalline SiC compact having a diameter of 150 mm and a thickness of 0.4 mm. This was obtained as the polycrystalline SiC compact according to Example 1.
[0057] (Examples 2 to 8 and Comparative Examples 1 to 3) A polycrystalline SiC film was formed in the same manner as in Example 1. However, the film formation conditions were changed as shown in Table 1.
[0058] (Evaluation method) The polycrystalline SiC compacts thus obtained were measured for (111) peak intensity ratio, carrier density, Hall mobility, nitrogen concentration (SIMS N concentration), average crystal grain size, and resistivity. The methods for measuring each value are described below.
[0059] (111) peak intensity ratio The X-ray diffraction pattern at the center of the polycrystalline SiC compact was measured by the 2θ / θ method using a Shimadzu XRD-6000 under the following conditions. Cu target Voltage: 40.0kV Current: 20.0mA Divergence slit:1.00000deg. Scattering slit: 1.00000deg. Receiving slit: 0.30000mm Scan range: 20,000 deg. or more and 80,000 deg. or less Scan speed: 4.0000deg. / min. Sampling pitch: 0.0200 deg. Preset time: 0.30sec. For the obtained X-ray diffraction pattern, background correction was performed appropriately, and the diffraction peak intensity in the diffraction angle 2θ range of 35.3 deg. to 36.0 deg. was determined as the peak intensity of the SiC (111) plane of 3C-SiC.
[0060] Similarly, the diffraction peak intensity in the diffraction angle 2θ range of 41.1 deg. to 41.8 deg. was determined as the peak intensity of the SiC (200) plane.
[0061] Similarly, the diffraction peak intensity in the diffraction angle 2θ range of 59.7 deg. to 60.3 deg. was determined as the peak intensity of the SiC (220) plane.
[0062] Similarly, the diffraction peak intensity in the diffraction angle 2θ range of 71.5 deg. to 72.3 deg. was determined as the peak intensity of the SiC (311) plane.
[0063] The total value of the diffraction peak intensities of the SiC(111), SiC(200), SiC(220), and SiC(311) planes was calculated, and the ratio of the diffraction peak intensity of SiC(111) to the total value was calculated as the (111) peak intensity ratio.
[0064] (carrier density, hall mobility) The Hall voltage and VanderPauw resistivity were measured using a Toyo Corporation Resistest8200, and the carrier density and Hall mobility were calculated (Hall effect measurement). The Hall effect measurement was performed under the following conditions after cutting the sample into a size of about 10 mm x 10 mm x 0.5 mm and forming an In electrode. Applied magnetic field: 1T Applied current: 1.0×10 -6 A Measurement temperature: room temperature (295K)
[0065] (Nitrogen concentration) The nitrogen content in the polycrystalline SiC compact was measured using an ATOMIKA SIMS-4000.
[0066] (Average grain size) The EBSD method was used to obtain a crystal orientation map for the normal direction of the main surface of the polycrystalline SiC compact.
[0067] The measurement conditions were as follows. Pretreatment: Chemical mechanical polishing Equipment: FE-SEM JSM-7900F manufactured by JEOL EBSD OXFORD AZtecHKL Image analysis software AZtec Crystal Measurement conditions: Voltage: 20kV Tilt angle: 70° Measurement area: 800μm×600μm Measurement interval: 1.4μm Evaluation target crystal system: 3C type SiC (space group 216) When measuring particles with an average particle size smaller than 5.5 μm under the above conditions, the analysis becomes unstable and accurate analytical results cannot be obtained, so in that case it is deemed "evaluation not possible."
[0068] Using the crystal orientation map measured above, the area of each single region was multiplied by the total area of the observation region (800 μm × 600 μm) and the sum of these values was calculated to obtain the average cross-sectional area of the crystal grains (area fraction method). The diameter of a circle with the same area as the average cross-sectional area of the obtained crystal grains was calculated to calculate the average crystal grain size. Specifically, the average crystal grain size was calculated by analyzing using image analysis software attached to the EBSD device.
[0069] For the crystal orientation map, measurements were taken at three points on the same measurement surface, the average crystal grain size was calculated for each point, and the average value of the three points was taken as the average crystal grain size for that measurement surface.
[0070] The positional relationship of each crystal orientation map was as follows: Find the center point of the measurement area on the first crystal orientation map. Measure the second crystal orientation map by moving a point in the visual field by 2000 μm or more and 4000 μm or less from that center point in any direction as the new center point. Measure the third crystal orientation map by moving a point in the visual field by 2000 μm or more and 4000 μm or less from the center point of the measurement area on the second crystal orientation map as the new center point.
[0071] The measurements were performed on both the front and back surfaces, and the larger value was determined as the average crystal grain size of the sample, with the threshold value being 10°.
[0072] (Volume resistivity measurement) The volume resistivity of the polycrystalline SiC compact was measured by a four-probe method in accordance with JIS K 7194. Specifically, a Loresta GP MCP-T610 manufactured by Mitsubishi Chemical Analytech Co., Ltd. was used to measure the volume resistivity.
[0073] (Discussion of results) As shown in Tables 1 and 2, the polycrystalline SiC bodies according to Examples 1 to 8 were formed under conditions of a film formation rate of 15 μm / hr or more and 60 μm / hr or less and a residence time of 10 seconds or more and 100 seconds or less. As shown in Table 2, the polycrystalline SiC bodies according to Examples 1 to 8 had low volume resistivities. In particular, Examples 2 to 8 had extremely low volume resistivities (specifically, 0.0074 Ω·cm or less). The average crystal grain size of the polycrystalline SiC bodies according to Examples 1 to 8 was 5.5 μm or more and 25.0 μm or less, and it was confirmed that the crystal grain size of the polycrystalline SiC bodies was within a specific range. In addition, the nitrogen concentration was 0.27×10 19 pieces / cm 3 More than 5.4×10 20 pieces / cm 3 The product of carrier density and Hall mobility was 4.0×10 20 pcs / cmVsec or more 100×10 20 The number of cells per cmVsec was less than 100.
[0074] On the other hand, in Comparative Example 1, where the deposition rate was 602 μm / hr, the average particle size could not be evaluated, and the product of carrier density and Hall mobility was 3.2 × 10 20 The number of particles / cmVsec was smaller than those in Examples 1 to 8, and the volume resistivity also exceeded 0.0200 Ω·cm.
[0075] Similarly, in Comparative Example 2 in which the deposition rate was 911 μm / hr, the average crystal grain size was also unmeasurable.
[0076] In Comparative Example 3, in which the film formation rate was 10 μm / hr, the average particle size was 27.3 μm, which was larger than those in Examples 1-8.
[0077] [Table 1]
[0078] [Table 2] [Industrial Applicability]
[0079] The large crystal grain size reduces the volume resistivity, making the material suitable for use as a heater or the like in semiconductor manufacturing equipment components. [Explanation of symbols]
[0080] 1. CVD reactor 2 mixer 3 Base material 4 Nozzles 5 Flowmeter 6. Carrier gas 7. Raw gas 8. Nitrogen-containing gases
Claims
1. The average crystal grain size is 5.5 μm or more and 25.0 μm or less, Nitrogen concentration is 0.27 x 10 20 pieces / cm 3 Above 5.4 x 10 20 pieces / cm 3 is as follows: The product of carrier density and Hall mobility is 4.0×10 20 pieces / cmVsec or more 100×10 20 pcs / cmVsec or less, Polycrystalline SiC molded body.
2. The polycrystalline SiC compact according to claim 1 , having a volume resistivity of 0.0200 Ω·cm or less.
Citation Information
Patent Citations
Silicon carbide polycrystalline substrate, method of manufacturing silicon carbide polycrystalline film, and method of manufacturing silicon carbide polycrystalline substrate
JP2020111495A
POLYCRYSTALLINE SiC COMPACT AND PRODUCTION METHOD THEREOF
JP2021054666A
POLYCRYSTALLINE SiC COMPACT
JP2021054667A
Silicon carbide polycrystalline film, and manufacturing method and deposition apparatus therefor
JP2021082765A
Polycrystalline sic molded article and method for producing same
WO2023171270A1